Prevalence and associated factors of vitreoretinal interface disorders using multicolour OCT among Chinese population in Fujian eye study - Li, Yang; Wang, Bin; Luo, Xiangdong; Zhang, Mingqin; Hu, Qinrui; Li, Xiaoxin (Scientific reports, 2025)
The aim of this study was to determine the prevalence, associations and ROC prediction of vitreoretinal interface disorders (VRI) among residents aged 50 years and older in Fujian Eye Study.The Fujian Eye Study is a population-based cross-sectional eye study in Fujian province, Southeast China. Residents aged 50 years and older were enrolled and did the questionnaire, physical and ophthalmological examinations. Multicolor OCT was used for high-resolution imaging of central retina in both eyes. Stata/SE 15.1 software was used for statistic analysis, a multivariate logistic regression model was used to identify associated factors for high myopia and the ROC curve analysis was used to verify the credibility.A total of 8173 residents were finally included in this study. The prevalence of VRI was 8.99% (95%CI: 8.37–9.61%), including 93.61% (95%CI: 91.84–95.37%) with ERM, 14.56% (95%CI: 12.01–17.11%) with any type of macular hole (MH) in at least one eye, and 2.45% (95%CI: 1.33–3.57%) with vitreoretinal traction (VRT). ERM was the most common type of VRI. Multiple logistic regression showed urban residency and coastal location were independently associated with VRI.The prevalence of VRI was high among Chinese adults, and ERM was the most common type of VRI. VRI was associated with urban residency and coastal location. This study provided the population-based data on the prevalence of VRI disorders in the Chinese elderly and filled in the global data.